2011
DOI: 10.4269/ajtmh.2011.10-0528
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Innovative, Affordable, and Open-Source Short Message Service–Based Tool to Monitor Malaria in Remote Areas of Uganda

Abstract: Quality health management requires timely and accurate data, and paper-based reporting does not fill this role adequately. The introduction of malaria rapid diagnostic tests and the availability of wireless communications present an opportunity to open direct data transmission and feedback between peripheral health workers and central managers. In November 2009, the Uganda Ministry of Health deployed a short message service–based reporting system in two districts. At a set-up cost of $100/health facility, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 10 publications
3
114
2
Order By: Relevance
“…Only 7% of broadband subscriptions in low-income countries have broadband speeds of 10 Megabits per second or higher (Table 1) [2], and multiple studies cite this poor network connectivity as a challenge [22–24]. These problems are seen even where mobile infrastructure is better developed than in many LMICs; in an urban South African image-based burn care pilot, transmission of images 1MB in size used up to 50MB of data as the app continually tried to push the image to the server, only to be interrupted multiple times prior to completion as the network dropped (Pajat Solutions Oy F, Personal communication from the app host 2016 Dec 6).…”
Section: Technological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 7% of broadband subscriptions in low-income countries have broadband speeds of 10 Megabits per second or higher (Table 1) [2], and multiple studies cite this poor network connectivity as a challenge [22–24]. These problems are seen even where mobile infrastructure is better developed than in many LMICs; in an urban South African image-based burn care pilot, transmission of images 1MB in size used up to 50MB of data as the app continually tried to push the image to the server, only to be interrupted multiple times prior to completion as the network dropped (Pajat Solutions Oy F, Personal communication from the app host 2016 Dec 6).…”
Section: Technological Considerationsmentioning
confidence: 99%
“…Pilot programs often have funding for the initial development and study, but if they do not plan and budget for ongoing app maintenance then they are unlikely to go to scale. Such a pilot in Kenya found that the cost of technical support needed for their malaria surveillance program would be around GBP 260 per month, which while not a prohibitive cost can stop wider uptake if it is not budgeted appropriately [24]. In a Chinese pilot, low smartphone ownership rates were overcome by issuing participants with phones preloaded with the application; unfortunately the project leads did not foresee that updating the app would require them to purchase new phones and reissue them to all of their front-line users, making the project unsustainable [25].…”
Section: Technological Considerationsmentioning
confidence: 99%
“…23 Mobile phones have been widely used in recent years to enhance data management, 24 and improve communication among providers. 25 Positive influences on health have been shown at a system level in low-resource settings. 26 Phones have been demonstrated to have significant impact on adherence to therapeutic regimens and on anti-infective clinical outcome indicators in countries such as Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…In some remote parts of Africa, landline phones, fast internet access, computers and paved roads are not readily available for the effective transfer of disease information [48]. Also, mobile phones and short message service (SMS) technology can form the basis of synchronized disease detection systems and integrated intervention efforts [49]. These communication tools can allow researchers to effectively collect and share data and enhance the routine reporting of malaria parameters such as antimalaria drug supplies at health facilities [49].…”
Section: Vector and Epidemiological Researchmentioning
confidence: 99%
“…Also, mobile phones and short message service (SMS) technology can form the basis of synchronized disease detection systems and integrated intervention efforts [49]. These communication tools can allow researchers to effectively collect and share data and enhance the routine reporting of malaria parameters such as antimalaria drug supplies at health facilities [49]. Nevertheless, more research is needed on the effect of economic growth on malaria elimination, on countrylevel health systems and circumstances and on their readiness to introduce and sustain novel programs and interventions [34].…”
Section: Vector and Epidemiological Researchmentioning
confidence: 99%